2018
DOI: 10.1177/1055665618760619
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health–Related Quality of Life of Children Born With Orofacial Clefts in Ethiopia and Their Parents

Abstract: The Amharic translation of the COHIP appears appropriate for use with families in Ethiopia. Both parents and patients reported OH-RQoL at similar levels as other international populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
4
18
0
Order By: Relevance
“…We did not find differences between parent and child’s QOL scores and our findings are similar to Abebe et al (2018), who found no significant difference between parent and child questionnaires; however, our results differ from Barr et al (2007) who found significant differences between parent and child reports for swallowing problems, with children perceiving a greater degree of impact. Our largest nonsignificant mean differences were for the subscale situational difficulty.…”
Section: Discussionsupporting
confidence: 70%
“…We did not find differences between parent and child’s QOL scores and our findings are similar to Abebe et al (2018), who found no significant difference between parent and child questionnaires; however, our results differ from Barr et al (2007) who found significant differences between parent and child reports for swallowing problems, with children perceiving a greater degree of impact. Our largest nonsignificant mean differences were for the subscale situational difficulty.…”
Section: Discussionsupporting
confidence: 70%
“…Also Reissmann et al found that parents' perception of their children OHRQoL is not accurate enough to detect problems in children age ranged between 7 and 17 years [27]. In contrast, other studies reported no differences between children and their caregivers' perceptions in any scale and the overall COHIP scores [20,22,28,29].…”
Section: Discussionmentioning
confidence: 98%
“…Bos et al [19] found that Parents' reports on their children's OHRQoL were not in agreement with reports of cleft lip and/or palate patients. In comparison, many previous studies reported no difference between children and caregivers' perceptions of their child's OHRQoL in any subscales and overall scores of COHIP [20][21][22]. Evaluation of OHRQoL response agreement between children and their caregivers' can also be helpful as healthcare providers seek methods of estimating the OHRQoL of children who are either mentally or physically unable to complete a questionnaire [22].…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with the findings of authors who show that surgical closure of oral clefts often restores oral health and function to acceptable levels. [11][12][13] In contrast there was a significant difference in the social domain of the scale between the cleft and control groups. This finding is interesting as it suggests that the restoration of oral health and oral function alone is not sufficient to overcome the social and emotional challenges of cleft lip and palate.…”
Section: Discussionmentioning
confidence: 75%
“…11 There have been several attempts to use parental questionnaires to examine the OHRQoL of children with cleft lip and palate, both before and after the surgery. [12][13][14][15] However, there are no data on the impact that PNAM can have on the QHRQoL. There has also been no attempt made to understand the impact of PNAM on the OHRQoL of children with cleft lip and palate.…”
Section: Introductionmentioning
confidence: 99%